GCC banks liquidity and financial performance: does the type of financial system matter? - Zaroug Bilal; Abdullah AlGhazali; Ahmed Samour (Future Business Journal)
Abstract This study examines whether the type of financial structure in the GCC influences the relationship between liquidity risk and banks’ performance from 2007 to 2021. By employing fixed effects and fully modified ordinary least squares (FMOLS), we find that the impact of liquidity risk on bank profitability differs among bank-based and market-based systems. Specifically, the results show that the profitability of banks operating in bank-based countries is positively influenced by the liquidity risk compared to their counterparts. The study also demonstrates that the global financial crisis increases banks’ profitability in the bank-based financial system. Furthermore, the results show that gross domestic product growth (GDPG) determines banks’ financial profitability in the banks-based market. This study offers some important implications for policymakers to consider the type of financial system to stimulate bank stability.